External validation of BIA equations to estimate appendicular skeletal muscle mass in older adults: Importance of the bias analysis and derivation of correction factors to achieve agreement - Cáñez-Ríos, María; Esparza-Romero, Julián; González-Arellanes, Rogelio; Ramírez-Torres, Maribel; Figueroa-Pesqueira, Guadalupe; Urquidez-Romero, René; Rangel-Peniche, Diana Beatriz; Alemán-Mateo, Heliodoro (Frontiers in Nutrition, 2022)
There are several equations based on bioelectrical impedance analysis (BIA) to estimate with high precision appendicular skeletal muscle (ASM). However, most of the external validation studies have reported that these equations are inaccurate or biased when applied to different populations. Furthermore, none of the published studies has derived correction factors (CFs) in samples of community-dwelling older adults, and none of the published studies have assessed the influence of the DXA model on the validation process. This study assessed the agreement between six BIA equations and dual-energy X-ray absorptiometry (DXA) to estimate ASM in non-Caucasian older adults considering the DXA model and proposed a CF for three of them. This analysis included 547 non-institutionalized subjects over 60 years old from the northwest of Mexico who were physically independent and without cognitive impairment: 192 subjects were measured using DXA Hologic, while 355 were measured by DXA Lunar. The agreement between the equations and DXA was tested considering the DXA model used as a reference method for the design of each equation, using the Bland and Altman procedure, a paired t test, and simple linear regression as objective tests. This process was supported by the differences reported in the literature and confirmed in a subsample of 70 subjects measured with both models. Only six published BIA equations were included. The results showed that four equations overestimated ASMDXA, and two underestimated it (p<0.001, 95% CI for Kim’s equation: -5.86 – -5.45, Toselli’s: -0.51– -0.15, Kyle’s: 1.43–1.84, Rangel-Peniche’s: 0.32–0.74, Sergi’s: 0.83–1.23, and Yoshida’s: 4.16–4.63 kg). However, Toselli’s, Kyle’s and Rangel-Peniche’s equations were the only ones that complied with having a homogeneous bias. This finding allowed the derivation of CFs, which consisted of subtracting or adding the mean of the differences from the original equation. After estimating ASM applying the respective CF, the new ASM estimations showed no significant bias and its distribution remained homogeneously distributed. Therefore, agreement with DXA in the sample of non-Caucasian was achieved. Adding valid CFs to some BIA equations allowed to reduce the bias of some equations, making them valid to estimate the mean values of ASM at group level.